2022
DOI: 10.1002/tqem.21852
|View full text |Cite
|
Sign up to set email alerts
|

Vermistabilization of fecal sludge with organic enriched substrates for compost production using two earthworm species (Eisenia foetida and Eudrilus eugeniae)

Abstract: Developing countries are facing high generation of fecal sludge without adequate systems for proper treatment, leading to detrimental effects on the environment from its disposal. An emerging and innovative option in curbing this problem is the use of epigeic earthworm species to stabilize the waste into vermicompost, a value‐added resource. Substrate enrichment techniques can be applied to promote the sustainability and effectiveness of the vermicomposting process. This study was therefore carried out to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Results of earthworm mortality recorded in the treatments are lower than that recorded in previous studies [ 9 , 16 , 17 ] and this could be due to the aerobic conditions caused by the presence of the macrophytes. Anaerobic and anoxic conditions are major sources of worm mortality Results from this study demonstrated that the vermibed in the MAV systems did not only facilitate the wastewater treatment process but also maintained the earthworm mortality below 10%.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Results of earthworm mortality recorded in the treatments are lower than that recorded in previous studies [ 9 , 16 , 17 ] and this could be due to the aerobic conditions caused by the presence of the macrophytes. Anaerobic and anoxic conditions are major sources of worm mortality Results from this study demonstrated that the vermibed in the MAV systems did not only facilitate the wastewater treatment process but also maintained the earthworm mortality below 10%.…”
Section: Discussioncontrasting
confidence: 81%
“…In the treated effluents, TDS, TSS, chlorides, turbidity and DOC were consistently reduced over the sampling period and this could be attributed to the actions of the macrophytes and earthworms. Macrophyte roots and vermibeds are capable of trapping the organic and inorganic solids where they are biologically processed by earthworms and microbes [ 16 , 17 ]. Macrophyte roots houses denitrifying bacteria and other microorganisms that assimilate organic matter using C as an electron donor [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13,14 In vermifiltration, contaminants are removed by filtration and a microbial layer formed on the filter bed contributes to their degradation. 15,16 The contaminants are retained on the filter beds in the form of solids and they are consumed and converted into humus by the earthworms. 14,17 Aeration is increased in the filter bed by the borrowing action of earthworms.…”
Section: Introductionmentioning
confidence: 99%